2007
DOI: 10.1007/s00436-007-0732-3
|View full text |Cite
|
Sign up to set email alerts
|

Zschokkella helmii n. sp. (Myxozoa: Myxosporea), a new parasite of marbled spinefoot Siganus rivulatus (Forsskal 1775), Red Sea, Egypt: light and transmission electron microscopy

Abstract: Zschokkella helmii n. sp., a new parasite of Siganus rivulatus from the Red Sea, Egypt, was described using light and transmission electron microscopy. However, the infection was severe; single "histozoic" plasmodium was encountered in the gallbladder wall. Spores are ellipsoid with 9-11 valvar striations. Spore mean length is 10.8 microm (10.0-11.0), while the spore mean width is 7.5 microm (7.0-8.0). Polar capsules are nearly round with a diameter of 2.2 microm (2.0-3.0) and have five filaments. Ultrastructu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Morphological similarity was found with Zschokkella nilei Abdel‐Ghaffar et al . ,b; from the kidney of the Nile tilapia, Oreochromis niloticus (L.), from Egypt; with Z. acheilognathi Kudo, 1916, infecting the gall bladder of the Japanese bitterling, Acheilognathus lanceolatum (Schlegel), from Japan (cited by Lom & Dykova ); with Z. mugilis Sitjà‐Bobadilla & Alvarez‐Pellitero () described originally from the gall bladder of the thin‐lip grey mullet, Mugil capito (Cuvier), and the leaping mullet, Liza saliens (Risso), in Spain and later described from the flathead mullet, Mugil cephalus (L.) (Ali ); and also with Z. egyptica Ali, Abdel‐Baki & Abdel‐Ghaffar from the gall bladder of the striped eel catfish, Plotosus lineatus (Thunberg), and the freckled goatfish, Upeneus tragula (Richardson), from Egypt.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Morphological similarity was found with Zschokkella nilei Abdel‐Ghaffar et al . ,b; from the kidney of the Nile tilapia, Oreochromis niloticus (L.), from Egypt; with Z. acheilognathi Kudo, 1916, infecting the gall bladder of the Japanese bitterling, Acheilognathus lanceolatum (Schlegel), from Japan (cited by Lom & Dykova ); with Z. mugilis Sitjà‐Bobadilla & Alvarez‐Pellitero () described originally from the gall bladder of the thin‐lip grey mullet, Mugil capito (Cuvier), and the leaping mullet, Liza saliens (Risso), in Spain and later described from the flathead mullet, Mugil cephalus (L.) (Ali ); and also with Z. egyptica Ali, Abdel‐Baki & Abdel‐Ghaffar from the gall bladder of the striped eel catfish, Plotosus lineatus (Thunberg), and the freckled goatfish, Upeneus tragula (Richardson), from Egypt.…”
Section: Discussionmentioning
confidence: 99%
“…Z. helmii Abdel‐Ghaffar, Ali, Quraishy, Entzeroth, Abdel‐Baki, Al Farraj and Bashtar 2008 is exceptional as it is histozoic in infecting the wall of gall bladder of the rabbitfish, Siganus rivulatus (Forsskal), from the Red Sea, Egypt (Abdel‐Ghaffar et al . ,b).…”
Section: Introductionmentioning
confidence: 99%
“…The highly pathogenic Zschokkella iceterica was reported in the gall bladder of wild Siganus luridus , Siganus rivulatus , and Siganus argenteus in Israel (Diamant and Paperna 1986 ; Diamant 1992 ) . Zschokkella helmii was recorded from the gall bladder of S. rivulatus from the Red Sea, Egypt (Abdel-Ghaffar et al 2008 ). Some unidentified ceratomyxids were observed from the gallbladder of S. rivulatus from Israel (Diamant 2010 ) and Egypt (Abdel-Ghaffar et al 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…Zschokkella helmii was recorded from the gall bladder of S. rivulatus from the Red Sea, Egypt (Abdel-Ghaffar et al 2008 ). Some unidentified ceratomyxids were observed from the gallbladder of S. rivulatus from Israel (Diamant 2010 ) and Egypt (Abdel-Ghaffar et al 2008 ). An unidentified Ortholinea species from the urinary bladder of S. rivulatus caught off Israeli waters (Diamant 2010 ) and Ortholinea saudii was isolated from the kidney of S. rivulatus from the Kingdom of Saudi Arabia off the Red Sea (Abdel-Baki et al 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…(Desser and Paterson 1978). However, the plasmodia of other myxosporean species may exhibit a single-unit membrane like Myxobolus exiguus (Pulsford and Matthews 1982), Kudoa lunata (Lom and Dyková 1988) and Zschokkella helmii (Abdel-Ghaffar et al 2008). Current and Janovy (1978) concluded that the differences in the nature of the plasmodium wall are tissue-dependent.…”
Section: Electron Microscopymentioning
confidence: 99%